The Pathogenicity of Actinomyces naeslundii is associated with polymicrobial interactions: A systematic review - Nurul Alia Risma Rismayuddin; Wan Nur Fatihah Wan Mohd Kamaluddin; Mohd Hafiz Arzmi; Ahmad Faisal Ismail; Edre Mohammad Aidid; Noratikah Othman (Wolters Kluwer Medknow Publications, 2020)
The aim of this systematic review was to demonstrate how the oral pathogenicity of Actinomyces naeslundii is associated with its interactions with other microbes in the oral microbiome. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA-P) 2015 protocol was used for this review. Articles published between January 2010 and February 2020 were searched in the PubMed, Web of Science, Science Direct, and Scopus databases. Articles included in the final analysis mainly discuss the symbiotic relationship of A. naeslundii with other oral microbes. The findings show that A. naeslundii is not directly involved in oral pathogenesis; instead, initial tooth surface colonization is promoted by polymicrobial interactions in the oral microbiome in which A. naeslundii participates.